Is transformation surviving? - Daly, Michael (School of Economics, 2016)
Recent political events in South Africa have emphasized the importance of faculty diversity. Very little research has considered why it is the case that 20 years after the end of Apartheid, only 14% of professors are black. Or, why the University of Cape Town does not have a single black South African woman who is a full professor. Is it the case that black faculty are discriminated against during the hiring process or is it the case that black faculty depart at significantly higher rates than white faculty as sometimes suggested? Further, how do race, education and institutional factors interact in determining diversity levels? Survival analysis methods coupled with a novel data-set consisting of detailed administrative employee records, proxies for performance and various socio-economic variables are employed to test various hypotheses related to these questions. The findings suggest that the level of diversity is of secondary importance to an employee's race when determining the likelihood of survival at the University of Cape Town. In addition, findings suggest that the university is performing far better in terms of gender equality than racial equality. Overall, race matters, not only through a direct correlation between employee race and tenure length, but also through indirect effects where employees who differ significantly from others in their respective faculty (in terms of race, tenure, age, education and gender) face increased rates of departure from the work place.